Cell penetrating peptides for in vivo molecular imaging applications. - Kersemans, V; Kersemans, K; Cornelissen, B (2008)
Cell penetrating peptides (CPPs) are a relatively new class of peptides that have the promising capability to cross cell membranes. While details remain to be resolved, various non-receptor-mediated endocytic pathways likely contribute most to the cell penetrating properties of these peptides. CPPs have been used to deliver many different cargos - ranging from radionuclides and other peptides to antibodies and nanoparticles - into cells. Besides many different drug delivery applications, CPPs have also seen a limited use in molecular imaging. Molecular imaging of intracellular and intranuclear targets, by techniques such as SPECT, PET, optical imaging, and MRI, relies heavily on the delivery of contrast agents to the cytoplasm and/or nuclei of the target tissue. Therefore, the number of applications in molecular imaging of intracellular targets has remained relatively low, because of the effective barrier presented by the cell membrane. One of the key strategies to overcome this challenge is the introduction of membrane-transducing peptides in the design of new contrast agents. This review presents an overview of the literature on CPPs, focusing on their use for molecular imaging. Applications using proteins and peptides, DNA/RNA, and CPP-loaded cells as the imaging agents will be looked at. Moreover, the difficulties and pitfalls regarding the use of CPPs in molecular imaging will be discussed.